Assessment of sea lice infection rates on wild populations of salmonids in Arnarfjörður, Iceland - Karbowski, Niklas, 1991- (2015)
Verkefnið er lokað til 30.6.2017. Sea lice have had impacts of varying severity on both wild and farmed salmonids in the past and although research has focused on this particular parasite, problems are still present. Lepeophtheirus salmonis Krøyer is of special concern, as negative impacts on the host fish have been proven, which can threaten wild fish populations. While countries like Norway and Scotland were only able to react to the problems induced by sea lice epizootics, Iceland is in the position to take pre-emptive measures. The present study was a first step into this direction, as it assessed the infection rates on wild salmonids in Arnarfjörður, North-West Iceland. During the month of July and August fish were sampled by using gill nets at three different sites. Lice were counted, their life cycle stages determined and the results were compared to previous studies from other countries. This comparison showed that both prevalence and intensities for the sampled fish are similar to those values from fjords without salmon farms. An impact on infection rates from the existing farms in Arnarfjörður was not found, most lice seemed to mature in August and it was suggested that their offspring should be able to complete a full life cycle in the same year. Whether these results are valid for other parts of Iceland, has to be shown by future research and a more specific analysis, for example the use of hydrographic models or infection thresholds is recommended, especially if the salmonid aquaculture in Iceland continues to grow.